The Delta variant mutations in the receptor binding domain of SARS-CoV-2 show enhanced electrostatic interactions with the ACE2 - Shaimaa S. Goher; Fedaa Ali; Muhamed Amin (Elsevier, 2022)
The mutations in the receptor binding domain (RBD) of the SARS-CoV-2 are shown to enhance its replication, transmissibility, and binding to host cells. Recently, a new strain is reported in India that includes mutations (T478K, and L452R) in the RBD, which are possibly increasing the infection rate. Here, using Molecular Mechanics (MM) and Monte Carlo (MC) sampling, we show that the mutations in the RBD of the Delta variant of SARS-CoV-2 induced conformational changes in ACE2-E37, which enhanced the electrostatic interactions by the formation of a salt-bridge with SARS-CoV-2-R403. In addition, we observed that these mutations altered the electrostatic interactions of the salt-bridge formed between the RBD-T500 and the ACE2-D355, which reduced by more than 70% compared the to the WT.